PENGARUH EDUKASI DENGAN MEDIA POP UP BOOK TERHADAP TINGKAT PENGETAHUAN ANAK TENTANG PERSONAL HYGIENE PADA ANAK DI PANTI ASUHAN KRISTEN GBKP GELORA KASIH DESA SUKAMAKMUR SIBOLANGIT TAHUN 2023 - Brenda Marissa Chrisanty Peranginangin; Rostime Hermayerni Simanullang (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Background: Personal hygiene is an individual effort to maintain body cleanliness to prevent disease. Children tend to have poor personal hygiene due to a lack of knowledge and habitual clean living behavior from an early age. Increasing children’s knowledge about personal hygiene can be achieved through education using attractive media such as pop up books, which are visual and interactive, making it easier for children to understand. Research objective: To determine the effect of education using pop up book media on the level of children’s knowledge about personal hygiene at the GBKP Gelora Kasih Christian Orphanage, Sukamakmur Village, Sibolangit, in 2023. Method: This study used a Quasi-Experimental design with a One Group Pretest-Posttest Design Without Control Group approach. The population consisted of 58 children, and 37 respondents were selected using a purposive sampling technique. Data were collected using a personal hygiene knowledge questionnaire, and data analysis was performed using the Wilcoxon Signed Rank Test. Research results: The results showed that before education, the level of knowledge was in the good category (24.3%), fair (48.6%), and poor (27.0%). After education, it increased to good (70.3%), fair (21.6%), and poor (8.1%). The Wilcoxon Signed Rank Test obtained a p-value of 0.000 (<0.05), indicating a significant effect of education using pop up book media on children’s knowledge improvement regarding personal hygiene. Conclusion: There is an effect of education using pop up book media on the level of children’s knowledge about personal hygiene. Suggestion: It is recommended that orphanage staff and health workers use pop up book media as an educational tool to instill clean and healthy living habits in children.